Analisis Tematik Kebijakan Pengelolaan Sampah Berbasis Partisipatif Menuju Ekonomi Sirkular di Kota Malang - Mustika Anggraeni (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The literature closely links the concepts of participatory waste management (PSP) and circular economy (SE). SE in waste management aims to reduce waste, increase resource efficiency, and create a closed cycle for waste management, that need PSP. A clear policy framework is necessary to achieve it. Problem formulations of this research; the current waste policy framework's application, the extent of PSP and EM concepts in the policy framework, and (c) the implementation and the recommendations for these concepts in Malang City waste policy. This study employs the qualitative data analysis method to analyse waste management policy documents, focusing on thematic analysis. The evolution of policies in Malang City is more dynamic compared to the national level, particularly in adapting to rapidly changing conditions related to existing waste generation. While, the PSP-ES concept receives limited accommodation, where waste management still implements end-of-pipe practices, despite the government’s effort to implement 3R.